Ankle sprain injury rates and associated risk factors in young soccer players during a season - Kofotolis, N.; Kellis, E.; Doulgeri, S. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Injury risk factors in soccer (Kofotolis & Kellis 2007) have been extensively investigated. However, fewer studies examined young soccer players (Junge et al 2000). The purpose of this study was to examine ankle sprain injuries, associated factors and mechanisms in young soccer players. Thirty-one (male) teams were observed during a oneyear period. Ankle sprains injury incidents, participation time loss, injury mechanisms and ankle region injured were recorded in games and practice sessions using questionnaires. A total of 677 athletes who sustained 38 ankle injuries were recorded. Of these, 26 (68.4%) were ankle sprain injuries with over 46.2 % of sprains involving anterior talofibular. Ankle injuries led to a total of 223.7 training sessions lost, with an average time loss per injury equal to 8.6 sessions. There were 40.443 hours of exposure, of which 28.758 (71.1%) were in practice and 11.685 (28.9%) in games. Most injuries (57.7%) were contact (p< 0.05). Of these, 72.7% were due to player contact. A 46.6% of noncontact ankle sprains occurred during running. The injury rate for this particular sample of young players was 0.93 per 1000 hours of exposure. This rate is lower compared with that reported for older professionals (Kofotolis and Kellis, 2007). As most ankle sprains occur through player contact, appropriate preventive measures should be taken to reduce impacts from contacts.